Studies on luminous Vibrio harveyi isolated from Penaeus monodon larvae reared in hatcheries in Andamans - Shome, Rajeshwari; Shome, B R; Soundararajan, R (Indian Journal of Fisheries, 2011)
A small prawn hatchery unit, established recently at the Central AgriculturalResearch Institute, Andaman, to produce prawn seed mainly of tiger prawn,Penaeus monodon, encountered the problem of luminous bacteria (LB) inrearing tanks, attacking at larval developmental stages. Detailed bacteriologicalinvestigation revealed high bacterial counts in intake source of sea water,filter bed filtered sea water, maturation and larval rearing tanks and lowbacterial counts in slow sand filtered -UV- radiation treated - again slow sandfiltered sea water. The LB could be isolated from intake sea water usingDunlop selective media suggesting that the main source of infection was fromintake sea water. The LB were also isolated from filter bed sea water,maturation tanks and nauplii stages of larval development. Four LB isolateshave been identified by morphological, cultural and various biochemical testsas luminous Vibrio harveyi. They were found to be sensitive to seven antibioticsand resistant against 11 others when tested by in vitro antibiotic disc diffusiontest. However, the sensitive antibiotics, when used either as prophylactic ortherapeutic agents, did not have appreciable effect on the LB population. Thenon-effectiveness of the antibiotics might be related to the tendency of V.harveyi forming biofilms in rearing tanks. The processing of intake sea waterby filtration followed by UV treatment and again refiltration was found to bethe effective way to reduce the bacterial counts and thus, the luminous V.harveyi load in the hatchery unit.